Template‐Free Preparation of Volvox‐like CdxZn1−xS Nanospheres with Cubic Phase for Efficient Photocatalytic Hydrogen Production. Issue 3 (8th January 2014) - Zhou, Hangyue; Liu, Qingyun; Liu, Weimin; Ge, Jiechao; Lan, Minhuan; Wang, Chao; Geng, Jianxin; Wang, Pengfei
Abstract Volvox‐like CdxZn1−xS solid solutions with a cubic zinc blend structure were synthesized through a template‐free ethylene glycol process. Cd(Ac)2⋅2 H2O, Zn(Ac)2⋅2 H2O, and thiourea are used as the starting materials and dissolved in ethylene glycol. These reaction precursors and solvent not only contributed to control over the formation of the volvox‐like spherical geometry, but also exerted vigorous domination for existence of cubic‐phase CdxZn1−xS nanostructures. As‐prepared volvox‐like CdxZn1−xS nanospheres have a diameter of around 100 nm with extensional shells. These samples show excellent photocatalytic H2 evolution activity from water splitting under visible‐light irradiation without any cocatalyst or scaffolding, owing to their tunable band gap, cubic zinc blend structure, and unique hierarchical porous structure with a high surface area (as high as 95.2 m2 g−1).